Effect of special exercises skills according to Al-Phusegene system budding footballers Preparation - Mirza, Abedulnasir (Journal of Physical Education, 2014)
This study aimed to prepare exercises according to the system Alphusvegene and a proposal to develop a force rapid footballers rookies and the problem of search in the presence of obvious weakness in the level of force Rapid players junior football and this certainly will directly affect the performance of some basic skills in football, as Aaaked researcher that there is a consistent and energy system appropriate for him as well as non-use of assistive devices for that, and the objectives of the research preparation exercises according to energy systems for soccer players and to identify the impact of these exercises according to energy systems in developing some basic skills, and the imposition of Researcher to the presence of statistically significant differences between the results of both testspre and post in the two experimental groups development for the two experimental groups.